2016
DOI: 10.1136/bmjopen-2015-010780
|View full text |Cite
|
Sign up to set email alerts
|

Occupational outcomes following mild traumatic brain injury in Canadian military personnel deployed in support of the mission in Afghanistan: a retrospective cohort study

Abstract: ObjectiveDeployment-related mild traumatic brain injury (MTBI) occurs in a significant number of military personnel but its long-term impacts are unclear. This study explores the impact of deployment-related MTBI on continued fitness-for-duty, with the ultimate intent of identifying potential targets for intervention to attenuate its effects.ParticipantsConsisted of 16 193 Canadian Armed Forces (CAF) personnel who deployed in support of the mission in Afghanistan and completed an enhanced postdeployment screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…However, as opposed to severe traumatic brain injury (TBI) where peripheral blood biomarker concentrations can acutely fluctuate by several orders of magnitude ( Di Battista et al, 2016a ), the relatively modest changes observed in concussion are often more difficult to characterize. Moreover, concussions occur frequently in the athletic and military settings where injury commonly accompanies physical exertion ( Garber et al, 2014 , 2016 ). This presents both methodological and analytical challenges, as exercise itself elicits profound physiological and biochemical alterations, and many of these perturbations are similar to those seen in concussion and/or mild head trauma ( Reihmane et al, 2012 ; Cook et al, 2013 ; Koh and Lee, 2014 ; Stocchero et al, 2014 ; Bessa et al, 2016 ; Kaspar et al, 2016 ; He et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as opposed to severe traumatic brain injury (TBI) where peripheral blood biomarker concentrations can acutely fluctuate by several orders of magnitude ( Di Battista et al, 2016a ), the relatively modest changes observed in concussion are often more difficult to characterize. Moreover, concussions occur frequently in the athletic and military settings where injury commonly accompanies physical exertion ( Garber et al, 2014 , 2016 ). This presents both methodological and analytical challenges, as exercise itself elicits profound physiological and biochemical alterations, and many of these perturbations are similar to those seen in concussion and/or mild head trauma ( Reihmane et al, 2012 ; Cook et al, 2013 ; Koh and Lee, 2014 ; Stocchero et al, 2014 ; Bessa et al, 2016 ; Kaspar et al, 2016 ; He et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concussion spans all age groups and includes specialised subpopulations such as athletes and military personnel (1,2). Despite the high prevalence and societal burden, concussion pathophysiology is unclear (3).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD contributes heavily to medical discharge, though other mental disorders clearly also contribute [ 6 ]. Research on the contribution of TBI is limited; however, one study suggests a substantial contribution [ 7 ] while another similar study suggests minimal contribution [ 8 ] to disability. Amputations, though frequently disabling, represent only a small subset of all musculoskeletal problems, even in a war zone [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past research has been constrained by its focus on only a particular subset of the military population (e.g. deployed personnel [ 6 , 8 ]), a single condition (such as TBI [ 8 ]) or a single disability-related outcome (e.g. medical discharge [ 6 , 8 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation